The potential of hydrogen storage in depleted unconventional gas reservoirs: A multiscale modeling study. (15th May 2023) - Wang, Shihao; Chen, Fangxuan; Wu, Yu-Shu; Nasrabadi, Hadi
Abstract: Subsurface energy storage in depleted petroleum reservoirs is a promising technique to balance and optimize the utilization of energy resources. In this work, we numerically explore the possibility of storing excessive hydrogen gas in depleted unconventional gas reservoirs. Our study is a multiscale analysis. From the molecular (pore) scale, we investigate the thermodynamics and transport mechanism of the hydrogen gas in the nanopores of the unconventional reservoirs. Then based on the results of the pore scale, we conduct reservoir-scale simulations to quantitatively investigate the preferred cycling pressure, the effective fraction of cushion gas and the amount of storage capacity of unconventional reservoirs. We have discovered that, compared to conventional gas reservoirs, hydrogen stored in unconventional reservoirs maintains higher purity because of the differential adsorption effect of the nanopores. This feature makes depleted unconventional gas reservoirs appealing candidates for underground storage of the hydrogen gas. Highlights: Potentials of hydrogen storage in unconventional reservoirs are investigated. Molecular dynamics simulation and reservoir simulation are performed. The preferential adsorption of methane facilitates the storage of hydrogen. The hydraulically fractured region is the main contributor for hydrogen storage. The existence of nanopores improves the purity of produced hydrogen.